O „logiczności” katolickiej wiary w ujęciu J. Ratzingera/Benedykta XVI. Wybrane aspekty na kanwie dyskusji na temat relacji Kościoła wobec teorii ewolucji - Kiejkowski, Paweł (Poznańskie Studia Teologiczne, 2022)
In September 2006, a symposium on the subject of creation–evolution was held in Castel Gandolfo. It was an opportunity to present the views of Joseph Ratzinger/Benedict XVI on the theory of evolution. At the same time, the Pope pointed to the fundamental “truth” of Christianity. It is rooted in the creative Divine Logos made manifest in Jesus Christ. In many of his texts, Joseph Ratzinger patiently recalls the “rationality”, “logicality” of all creation, especially of man and human cognition. He pays special attention to the uniqueness of Catholic faith and theology, which is expressed in its rationality. The thought of the German theologian captivates with its accuracy, logic and precision. Hence the suggestion of this paper. It presents three important texts, published at different times, on the subject of the “logic” of the Catholic faith.